ANALYSIS OF BUSINESS DEVELOPMENT STRATEGIES OR MSMES PEMPEK UTI TO PRESERVE TRADITIONAL FOOD - Dian Sudiantini; Daniel Panjaitan; Risqina Puteri; Syifa Fauziah (Nindikayla Institute, 2023)
This study aims to analyzea strategy in business development using qualitative methods. Qualitative method is a research procedure that can produce descriptive data in written or oral form from humans and observable behavior. Business development strategy is an action that requires management to be able to make decisions in developing the business to realize it. Micro, Small and Medium Enterprises (MSMEs) in Indonesia are priorities in Indonesia's economic growth and development. The object of this study is Pempek Uti MSMEs. Pempek uti UMKM is a home culinary business that sells traditional food typical of South Sumatra, namely pempek. The types of pempek offered are quite a lot and the price adjusts to the pockets of students and students. The data collection technique used in this study was to make an observation and questionnaire to the respondents. The results obtained in this study are that in their business development strategy, Pempek Uti MSMEs use digital marketing to build a brand image on these products. Digital marketing is through Whatsapp, Instagram, and Facebook. As for the survey results, the questionnaire data showed that most people are interested in pempek uti because it tastes good and the price is affordable